Anadolu (Hiti-Luvi) hiyeroglif yazıtlarında geçen tanrı, şahıs ve coğrafya adları = Divine, personal and geographical names in the Anatolian (Hittite-Luwian) hieroglyphic inscriptions. - Savaş, Savaş Özkan. (İstanbul)
lviii, 230 s.